Understanding the adsorption of iron oxide nanomaterials in magnetite and bimetallic form for the removal of arsenic from water - Boruah, Himangshu; Tyagi, Neha; Gupta, Sanjay Kumar; Chabukdhara, Mayuri; Malik, Tabarak (Frontiers in Environmental Science, 2023)
Arsenic decontamination is a major worldwide concern as prolonged exposure to arsenic (>10 µg L-1) through drinking water causes serious health hazards in human beings. The selection of significant, cost-effective, and affordable processes for arsenic removal is the need of the hour. For the last decades, iron-oxide nanomaterials (either in the magnetite or bimetallic form) based adsorptive process gained attention owing to their high arsenic removal efficiency and high regenerative capacity as well as low yield of harmful by-products. In the current state-of-the-art, a comprehensive literature review was conducted focused on the applicability of iron-based nanomaterials for arsenic removal by considering three main factors: (a) compilation of arsenic removal efficiency, (b) identifying factors that are majorly affecting the process of arsenic adsorption and needs further investigation, and (c) regeneration capacity of adsorbents without affecting the removal process. The results revealed that magnetite and bimetallic nanomaterials are more effective for removing Arsenic (III) and Arsenic (V). Further, magnetite-based nanomaterials could be used up to 4-5 reuse cycles, whereas this value was limited to 3 reuse cycles for bimetallic ones. However, most of the literature was based on laboratory findings using decided protocols and sophisticated instruments. It cannot be replicated under natural aquatic settings in the occurrence of organic contents, fluctuating pH and temperature, and interfering compounds. The primary rationale behind this study is to provide a comparative picture of arsenic removal through different iron-oxide nanomaterials (last twelve years of published literature) and insights into future research directions.